Critical systems : formal methods and automated verification : Joint 22nd International Workshop on Formal Methods for Industrial Critical Systems and 17th International Workshop on Automated Verification of Critical Systems, FMICS-AVoCS 2017, Turin, Italy, September 18-20, 2017, Proceedings /: formal methods and automated verification : Joint 22nd International Workshop on Formal Methods for Industrial Critical Systems and 17th International Workshop on Automated Verification of Critical Systems, FMICS-AVoCS 2017, Turin, Italy, September 18-20, 2017, Proceedings. (2017) - Unknown
No abstract available